Associations of inter-segmental coordination and treadmill walking economy in youth with cerebral palsy. (7th May 2021) - Kuntze, Gregor; Esau, Shane; Janzen, Leticia; Brunton, Laura; Nuique, Kate; Condliffe, Elizabeth; Emery, Carolyn
Abstract: This study investigated associations of thigh-shank coordination deficit severity and metabolic demands of walking in youth with cerebral palsy (CP) and their typically developing (TD) peers. Youth (ages 8–18 years) with hemiplegic and diplegic CP [Gross Motor Classification System (GMFCS) I-III] and their age (within 12 months) and sex-matched peers performed a modified six-minute-walk-test on a treadmill. Kinematics (Motion Analysis, USA, 240 Hz) and mass-specific gross metabolic rate (GMR; COSMED, Italy) were analyzed for minute two of treadmill walking. Thigh-shank coordination was determined using continuous relative phase (CRP) analysis. GMR was normalized using participant specific Froude numbers (i.e. GMREq ). Maximum and minimum CRP deficit angles (CRPMax, CRPMin ) were analysed in SPSS (IBM, USA) using paired samples t-tests with Bonferroni correction (p = 0.0125). Associations of knee extension angle deficit (KEDMax ) and coordination outcomes with GMREq (log) were assessed using multiple linear regression. Twenty-eight matched pairs were included, demonstrating significantly larger CRPMax for youth with CP [GMFCS I mean pair difference (98.75%CI) 8.2 (−0.1, 16.5), P = 0.013; GMFCS II/III 26.1 (2.3, 50.0), P = 0.008]. Joint kinematics and coordination outcomes were significantly associated with GMREq (P < 0.001), primarily due to CRPMax (P < 0.001), leading to a 1.7 (95%CI; 1.1, 2.4)% increase in GMREq for every degree increase in CRPMax . These findings indicate an association of thigh-shank coordination deficit severity and increasing metabolic demands of walking in youth with CP. CRP may be a clinically useful predictor of metabolic demands of walking in CP. Future work will evaluate the sensitivity of CRP to coordination and walking economy changes with surgical and non-surgical management.